Superhydrophobic and thermochromic VO2-Based composite coatings for energy-saving smart windows. (June 2022) - Pi, Jing; Li, Chun-Bo; Sun, Ren-Yi; Li, Lin-Yue; Wang, Fang; Song, Fei; Wu, Jia-Min; Wang, Xiu-Li; Wang, Yu-Zhong
Abstract: Architectural windows based on vanadium dioxide (VO2 ) that can regulate optical radiation by changing solar transmittance are of particular interest to energy conservation of buildings. Besides the critical contradiction of luminous transmittance ( T lum ) and solar regulation ability (Δ T sol ), as a smart window, antifouling property which also affects the optical performance is required to consider. Here, thermochromic and hydrophobic core-shell VO2 nanoparticles are prepared with tetraethyl orthosilicate and imethyloctadecyl [3-(trimethoxysilyl) propyl] ammonium chloride. With the adhesion effect of polydimethylsiloxane, the nanoparticles can be adhered on solid substrates. Compared with the neat VO2, the core-shell nanoparticles demonstrate increased ΔT sol (from 9.9% to 15.4%) and T lum (from 47.9% to 51.5%), presenting a well-balanced optical property. Moreover, the presence of long alkyl chain on the core-shell nanoparticles enables high anti-wetting and self-cleaning functions. Such a composite coating has excellent wetting resistance and self-cleaning properties, enhancing the applicability as intelligent windows. Graphical abstract: Image 1 Highlights: A superhydrophobic and thermochromic composite coating is prepared. Such composite coating presents a well-balanced optical performance. The coating displays high wetting resistance and environmental stability.